2021
DOI: 10.3390/ijerph182312783
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge of and Attitudes towards COVID-19 Prevention Techniques in Saudi Arabia: A Cross-Sectional Study

Abstract: The purpose of the study was to assess the community knowledge of and to obtain a broad overview of attitudes towards appropriate prevention techniques that are recommended by the Ministry of Health to prevent COVID-19 transmission in Saudi Arabia. Methods: A cross-sectional study using an online survey was conducted in Saudi Arabia between 1 May and 30 November 2020 to assess the community knowledge of and attitudes towards appropriate COVID-19 prevention techniques in Saudi Arabia. The study tool was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
1
1
1
Order By: Relevance
“…Yet, the majority were willing to comply with preventive measures if established and enforced by the government such as mandatory mask wearing, social distancing, and mandatory lockdowns. Our findings are in line with attitudes from Saudi Arabia which showed that most of the community was willing to stay at home (i.e., lock down) or avoid shaking hands to mitigate the spread of the virus, if enforced by the government (32). Perhaps most importantly from our findings is that, very few respondents mentioned vaccination as a preventative and disease control measure and few participants found the vaccine effective and protective, 12.5 and 32%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Yet, the majority were willing to comply with preventive measures if established and enforced by the government such as mandatory mask wearing, social distancing, and mandatory lockdowns. Our findings are in line with attitudes from Saudi Arabia which showed that most of the community was willing to stay at home (i.e., lock down) or avoid shaking hands to mitigate the spread of the virus, if enforced by the government (32). Perhaps most importantly from our findings is that, very few respondents mentioned vaccination as a preventative and disease control measure and few participants found the vaccine effective and protective, 12.5 and 32%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Another factor that might have contributed to this difference in knowledge may be due to the difference in age distribution, as compared to other studies. For example, in Saudi Arabia more than 92% of the sample of study were under the age of 49 whereas in our study 67% of the participants were above the age of 49 ( 32 ). Our findings showed that level of knowledge on different COVID-19 topics were varied.…”
Section: Discussioncontrasting
confidence: 64%
“… Almalki/Dec 2021 108 Knowledge, Attitudes, and Practices Toward COVID-19 Among the General Public in the Border Region of Jazan, Saudi Arabia: A Cross-Sectional Study 597 participants Online questionnaire Most study participants had good knowledge, positive attitudes, and effective practices toward COVID-19. AbuAlhommos/Dec 2021 109 577 individuals Online questionnaire A good level of knowledge/positive attitudes towards COVID-19 was observed. Continuous efforts should be maintained to sustain awareness among the public.…”
Section: The Searched Outcomesmentioning
confidence: 97%
“…Sehingga dipandang perlu membekali penderita penyakit kronis dengan pengetahuan tentang kemampuan menjaga kesehatan diri dan kemampuan melindungi diri dari penularan penyakit (de Lima Filho et al, 2021). Pengetahuan dan sikap masyarakat terhadap infeksi akan mempengaruhi ketaatan dan kemandirian dalam perilaku untuk menghindari infeksi (Abualhommos et al, 2021). Pengetahuan ini juga akan mendukung program pencegahan infeksi lain seperti imunisasi (Moeed et al, 2022) dan upaya pemenuhan gizi yang baik untuk ketahanan tubuh (Yuan et al, 2022).…”
Section: A Latar Belakangunclassified